Co-producing knowledge and care in team-based fieldwork in the Covid-19 era. Issue 4 (2nd October 2021) - Asante, Comfort; Burack, Sarah; Chileshe, Mutale; Hunleth, Jean
Abstract : In this article, we examine how the pandemic has led us to a dispersed and technologically mediated form of team-based fieldwork framed by an ethics of care. Covid-19 has changed the proximity of research teams and, thus, affected how teams are present for one another during challenging times, such as when researchers witness extreme suffering or death during a study. The four authors present reflections on collaborating on a caregiving study in a Zambian paediatric hospital during Covid-19. We describe a collaboration founded on a feminist ethics of care, co-production of knowledge, and attention to power dynamics between African academics and US academics, research assistants and established scholars. We do so through foregrounding the views and experiences of the research assistants, offering a glimpse into the experiential aspects of dispersed team-based research in a pandemic. The article offers insights into distanced, collaborative research across continents, including regular check-ins and radical listening; generous feedback, modelling and co-mentoring; and co-imagining our presence and futures. These serve as interventions into virtual collaborative work and also into collaboration in anthropology in general.